Insights into canine communication and interspecific misinterpretations - Nicolene Swanepoel (Communicare)
By providing background on ca· nine olfactory, auditory and visual communication, this paper hopes to clarify common human misin· terpretations of dog behaviour. Visual displays are subdivided into displays of rank (dominant and submissive), and displays of erno· tion (aggression and fear). Tail wagging, friendly communication, greeting behaviour in dogs. compared to the human handshake, as well as attention seeking behaviour are discussed. The influence of human selection in breeding on visual displays illustrates the effect of human interference in canine communication. The paper does not aspire to be recognised as a critical academical investigation, or to provide documentation of original research. It merely attempts to provide insight through basic theoretical comments, supported in part by existing literature, and in part by the author's own experience.